Dulaglutide-induced cerebral venous thrombosis in a patient with type 2 diabetes mellitus. (8th November 2018) - Rajput, Rajesh; Pathak, Vaibhav; Yadav, Pawan Kumar; Mishra, Sanat
Abstract : Though patients with diabetes mellitus are at a high risk of atherothrombotic events, every such event should not be attributed to the disease itself. We present a case of a patient with diabetes with headache and blurring of vision for 3 days. Brain imaging revealed right transverse sinus thrombosis and acute infarct of the right posterior parieto-occipital region, predominantly in the posterior cortical watershed zone. The patient was on subcutaneous dulaglutide for 3 weeks and was having nausea and vomiting. Various causes of cerebral venous thrombosis were ruled out with appropriate laboratory investigations. Finally, cerebral venous thrombosis was attributed to dulaglutide-induced nausea and vomiting which led to severe dehydration.